John Bartlow Martin papers - Martin, John Bartlow, 1915-1987.; Martin, John Bartlow, 1915-1987.; Martin, John Bartlow, 1915-1987.
Correspondence, memoranda, diaries and diary notes (1936-1961), speeches, writings, drafts, notebooks, research files, political campaign files, family and estate papers, financial and legal papers, printed material, and photographs; the bulk of the collection is dated 1939-1983. Documents Martin's career as a free-lance journalist specializing in crime stories and in articles (many later expanded and published as books) on social problems such as labor and prison reform, racial segregation, juvenile delinquency, and mental illness; his role as an advance man, speechwriter, and adviser to Democratic presidential candidates from 1952-1972, especially Adlai E. Stevenson II; and his appointment by John F. Kennedy and subsequent service as ambassador to the Dominican Republic. Includes research files for Martin's two-volume biography, The Life of Adlai Stevenson (1976-1977) and for the memoir of his experiences in the Dominican Republic, Overtaken by Events (1966). Also of note is Martin's draft of Newton N. Minow's "vast wasteland" speech (1961).
Correspondents include Edward L. Bernays, Clark M. Clifford, William O. Douglas, Harold Ober Associates, Marshall M. Holeb, John Houseman, Hubert H. Humphrey, Lyndon B. Johnson, Harry Keller, Edward Moore Kennedy, Robert F. Kennedy, Alfred A. Knopf, Eric Larrabee, Martin Lubow, Hugo Melvoin, Newton N. Minow, Bill D. Moyers, Francis S. Nipp, Arthur Meier Schlesinger, Jr., Adlai E. Stevenson II, Adlai E. Stevenson III, Robert W. Tufts, and John D. Voelker.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Geography and Map Division.
Library of Congress Music Division.
Library of Congress Serial and Government Publications Division.
Author, journalist, political adviser, and U.S. ambassador to the Dominican Republic.
Collection material in English.
Keywords: Bernays, Edward L., -- 1891-1995 -- Correspondence; Clifford, Clark M., -- 1906-1998 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Holeb, Marshall M. -- Correspondence; Houseman, John -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Keller, Harry -- Correspondence; Kennedy, Edward M. -- 1932-2009 -- Correspondence; Kennedy, John F. -- 1917-1963.; Kennedy, Robert F., -- 1925-1968 -- Correspondence; Knopf, Alfred A., -- 1892-1984 -- Correspondence; Larrabee, Eric -- Correspondence; Lubow, Martin, -- 1923- -- Correspondence; Melvoin, Hugo -- Correspondence; Minow, Newton N., -- 1926- -- Correspondence; Moyers, Bill D. -- Correspondence; Nipp, Francis S. -- Correspondence; Schlesinger, Arthur M. -- 1917-2007 -- Correspondence; Stevenson, Adlai E. -- 1900-1965.; Stevenson, Adlai E. -- 1900-1965 -- Correspondence; Stevenson, Adlai E. -- 1930- -- Correspondence; Tufts, Robert W., -- 1915- -- Correspondence; Voelker, John D. -- 1903- -- Correspondence; Harold Ober Associates -- Correspondence; Democratic Party (U.S.); African Americans -- Segregation; Crime writing; Diplomatic and consular service, American -- Dominican Republic; Political campaigns -- United States; Journalism -- United States; Juvenile delinquency -- United States; Labor movement -- United States; Mental illness -- United States; Presidents -- United States -- Election; Prisons -- United States; Social problems -- United States; Dominican Republic -- Politics and government -- 1961-; United States -- Politics and government -- 1945-; Ambassadors; Authors; Journalists; Political consultants